A cultural analysis of Generation Z’s perception of individualism and collectivisim in Turkish television commercials through a Hofstedian lens - Nilnur Tandaçgüneş Kahraman; Özlem Kalan (Connectist Istanbul University Journal of Communication Sciences)
Advertisements function as cultural texts that interact with society. A crucial factor influencing advertising and consumer behavior is generational culture. Generation Z, born into a digital age, exhibits distinct cultural characteristics and consumption patterns compared to previous generations. For this reason, understanding how younger generations interpret cultural codes in the digital age is a significant issue in communication studies. Türkiye, with its youthful population and extensive media consumption, offers a valuable context to explore this relationship between Generation Z and advertising. It is seen that the theme of individualism, which was prominent only in Western societies in the predecessors of intercultural studies, has evolved into a general characteristic in current studies on Generation Z. This study aims to understand how Generation Z growing up in Türkiye, which Hofstede defines as a collectivist society, perceives individualist and collectivist messages in advertisements, a cultural text. Television commercials of all Global System for Mobile Communication (GSM) brands serving in the country were determined as the research population. The research was designed in two stages. First, the advertisements identified through purposive sampling were coded as individual/collective through descriptive content analysis. The interactions of the focus group participants, selected by criterion sampling to represent Generation Z, with the advertisement messages were described according to their reception of individualism/collectivism codes. According to the results of the research; contrary to Hofstede’s prediction, the participants’ preferences, tendencies and approaches were found to be in common in the qualities belonging to individual culture.